Recruiting your own dream team relationships built to last lead to success built to last - Porras, Jerry I. (Pearson Education Pub. as FTPress Delivers, 2010)
"This Element is an excerpt from Success built to last: creating a life that matters (ISBN: 9780132287517) by Jerry Porras, Stewart Emery, and Mark Thompson. Create relationships that are "built to last": relationships that will make you more effective for a lifetime, whatever your role, job, or goals."--Resource description page.
Includes bibliographical references
Keywords: Success in business; Successful people; Succès dans les affaires; Gagneurs